Values of circulating molecular biomarkers (microRNAs) for the evaluation of renal failure during urgent abdominal sepsis anaesthesia - Bukauskas, Tomas; Kairytė, Monika; Mickus, Rytis; Puleikytė, Loreta; Macas, Andrius (Acta medica Lituanica, 2019)
Background. Micro-ribonucleic acids (miRNAs) are small non-coding molecules important for gene regulation and management of physiological processes (1). Alterations in the expression of miRNAs are potential novel biomarkers for many diseases (2). Materials and methods. Random patients who underwent emergency surgery for abdominal sepsis were enrolled into the study (N = 27). Patients were divided into three groups according to the renal function and into two groups depending on the presence or the absence of lethal outcomes during the hospitalization period. Relative expression levels of circulating serum miR-30d-5p, miR-23a-3p, miR-146a-5p were assessed with real-time quantitative polymerase chain reaction using the 2–ΔΔCt method and compared between the groups. Results. Expression levels of all three miRNAs did not differ significantly between patients with acute renal failure (ARF) (n = 8), chronic renal failure (CRF) (n = 8), and with a normal renal function (NRF) (n = 11). Estimated glomerular filtration rates (eGFR) were significantly lower (p = 0.016), the values of urea (p = 0.007) and red blood cell distribution width (RDW) (p = 0.001) were significantly higher in septic patients who died, but no significant correlation between RDW values and expression of miRNAs was found. Conclusions. The expression levels of serum miR-30d-5p, miR-23a-3p, miR-146-5p did not significantly differ between three groups of patients who developed ARF, had CRF, or retained NRF. No significant association between the RDW value and expression of miRNAs was noted.
Keywords: MiRNA; acute renal failure; chronic renal failure; RDW; sepsis